Individual and Community-Level Factors Associated With Intention to Use Contraceptives Among Reproductive Age Women in Sub-Saharan Africa - Desale Bihonegn Asmamaw; Habitu Birhan Eshetu; Wubshet Debebe Negash (Frontiers Media S.A., 2022)
Objectives: The present study identifies factors that affect intention to use contraceptives among married women in countries in sub-Saharan Africa.Methods: Secondary data analysis was conducted using Demographic and Health Surveys. A total of 334386 weighted sample women who were fecund were included in the analysis. Multi-level mixed-effect logistic regression analysis was fitted to identify individual and community level factors associated with intention to use contraceptives.Results: The prevalence of intention to use contraceptives was 45.76%. Age, educational status, and wealth quintile were factors affecting the intention to use contraceptives.Conclusion: Several individual and community level factors were associated with the intention to use contraceptives in SSA. Therefore, governmental and non-governmental organizations should consider these factors when implementing strategies.